Percepção intergeracional de paisagens urbanas: estudo de caso da comunidade dos Arturos - Kelly Aparecida de Souza Carneiro (2017)
When understanding a landscape, it is important to connect it to the historical, cultural, political, social and economic factors, specially regarding cities, where there is an overlapping of needs and interests. Considering this, the experience of a man and his perception about the environment in which he is inserted become two important factors. This way, the following study aimed at understanding what is the perception of the residents of the Arturos Community about the urban landscape and its place, as well as the factors of topofilia and topofobia that currently reverberate in everyday life. The study done with the Arturos Community assume that these factors represent a strong connection with the place, indicating topofilia, besides representing resistance as a reflex of the culture of the black people in the country. The methodology consisted of bibliographical and documental research, data collection and analysis about the town, the RMBH and the Arturos Community; question surveys with open questions and multiple choice questions, as well as the use of interviews based on the technique of Thematic History (directed to the Arturos Community); field observation and iconographical records, data organization and systematization for map creation, graphs, chants and other things. Regarding the relationship between the community and the town, the study was based on some experiences that affect the people, which are: traveling time in the urban territory, violence and the contact with the landscapes of the central areas. In the history of the Arturos it is possible to notice that they show how important it is to establish bonds with the place, with their ancestors, with their land, with their traditions, with their fights and resistance, revealing that they are family and at the same time they are citizens in search of adequate conditions of life. The results of the surveys revealed that: i) when the organization and the characteristics of the Arturos is portrayed, its intergenerating character is summoned; ii) the story of the city expansion and the story of the community integration intertwine; iii) the site, the neighborhood, the city and the foundation of the houses are part of the communitys identity; iv) the residents of the Arturos Community are individuals in a delayed living, highlighting, their condition as established; v) religion is a very important element in the relationship with the place, vi) although community life raises the feeling of protection, there are situations and areas that place the individual as vulnerable, indicating topofobias. However, the experiences of the Arturos are between the insider and outsider way of life, which place then between a countryside lifestyle and the new temporalities and espacialidades placed on them by the city, such as: the new interpersonal relationships; the (i)mobility of the urban means of transportation; the constant transformation of the spaces and landscapes; the feeling of strangeness towards the neighbor and the city; the fear of violence and, specially, the resistance towards preserving traditions, faith and values.